Aprender (n)a horta urbana : práticas e experiências em comunidade - Schmitt, Lilian Alves (2021)
The thesis presented here considers the analysis of a urban garden located at Lomba do Pinheiro neighbour, in Porto Alegre city, at the Rio Grande do Sul state in Brazil to understand how the learning process occurs community places. Our general aim to know the learning experiences in this context. We follow an ethnographic approach through participant observation, developed between 2017 and 2019, and through interviews with the apprentice group linked to the community initiative. We invoke an ontological idea of learning during the workflow based on the principle of participation in shared practices with other humans or non-humans. This perspective is about learning how to learn to be, live, and acquire skills while building bonds of belonging to an environmentally situated place and a community of practice. The shared and co-produced community experience throughout the research makes it possible to question the certainties and convictions of the subjects involved therein, it enables continuous discussion, providing a democratic experience that is characterized not by the prevalence of the will of a supposed majority, but by the exercise of doubt, for the possibility of exercising criticism. During the practices in those specifical community places, it was possible to observe the development of skills related to horticulture techniques in urban areas and learn about the experiences that cause shifts of a subjective nature, including developing both skills sensitive and political terms. We emphasize that it is with/in the practice of the experience of being a community that we also learn about its precariousness, contingency and need for review.